Ethical Leadership in Companies: The Key to Transforming Ordinary Routine into Extraordinary Actions - Casasola Rivera, Wilmer (2023)
The main objective of this paper is to analyze the relevance of ethical leadership in business, organizational and institutional contexts. The paper follows a systematic narrative research methodology. The paper proposes that the management of an organizational culture focused on ethical leadership can enable professional performance to achieve better results by transforming ordinary routine into extraordinary actions.